1998
DOI: 10.1002/pro.5560071014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a folding intermediate from HIV‐1 ribonuclease H

Abstract: The RNase H domain from HIV-1 (HIV RNase H) encodes an essential retroviral activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 60 publications
3
25
0
Order By: Relevance
“…The dimer that we observed in solution most likely results from domain swapping at the helix region (Figure 3). Previously, the helix region was observed to be unstable in the folding intermediate of the RNH fragment (57), suggesting that the helix can be swapped during the folding process. Indeed, unfolding of the WT RNH monomer in 6 M urea followed by re-folding at very high protein concentration in NMR buffer (> 10 mM) yielded almost exclusively Fraction #1 (data not shown), in line with earlier observations for other domain swapped dimers (52).…”
Section: Discussionmentioning
confidence: 99%
“…The dimer that we observed in solution most likely results from domain swapping at the helix region (Figure 3). Previously, the helix region was observed to be unstable in the folding intermediate of the RNH fragment (57), suggesting that the helix can be swapped during the folding process. Indeed, unfolding of the WT RNH monomer in 6 M urea followed by re-folding at very high protein concentration in NMR buffer (> 10 mM) yielded almost exclusively Fraction #1 (data not shown), in line with earlier observations for other domain swapped dimers (52).…”
Section: Discussionmentioning
confidence: 99%
“…Such a procedure assists conformational sampling and ensures that an enhanced representation of the solution state free energies is generated (29). Because the present restrained samplings enforce NMR observables (i.e., H/D exchange protection factors) that reflect fluctuations occurring in the millisecond timescale (and beyond) (21)(22)(23)(24), the resulting structural ensembles are particularly valuable for describing backbone dynamics relevant to the processes of protein folding and misfolding, which are those that affect the maintenance of protein solubility and are governed by events that typically occur in these timescales (34,35).…”
Section: Nmr Measurements Of Acpdro2mentioning
confidence: 99%
“…They showed that the mutated form remained capable of adopting a folded structure similar to that of the isolated wild-type domain; however, a urea denaturation study indicated that it was 2 kcal/mol less stable than the longer construct. Given a previous report of the stability of the RH domain of 3.7 kcal/mol [66], the loss of the two N-terminal residues represents a destabilization of RH’ by >50%.…”
Section: Dimerization-induced Structural Changesmentioning
confidence: 99%
“…Multiple studies indicate that in the absence of ligands, the C-terminal helix E of RH is largely disordered, freeing as many as 22 residues on each subunit to act as linkers to an IN dimer [66,71,119,120,121]. Alternatively, although there are five disordered residues at the N-terminus of the p51 monomer (PDB ID: 4KSE, [16]), formation of a PR-RT linker would require additional unraveling of the N-termini.…”
Section: Maturation Within the Virionmentioning
confidence: 99%